Through their eyes: enhancing teacher awareness of visual impairments via extended reality simulations (REALTER) - Barbieri, Mattia; Pennazio, Valentina; Sabatini, Silvio P.; Gori, Monica (Frontiers in Education, 2025)
IntroductionUnderstanding the lived experiences of students with visual impairments is essential for fostering inclusive educational practices. However, traditional teacher training often lacks experiential components that convey the functional impact of low vision. This study explores the use of gaze-contingent immersive simulation in extended reality (XR) to enhance teachers' awareness and empathy toward students with visual impairments.MethodsWe employed the REALTER system, a portable XR platform originally developed for visual rehabilitation and oculomotor research, to simulate juvenile macular degeneration. Eleven in-service teachers participated in task-based simulations replicating common classroom activities. The system introduced real-time, gaze-responsive visual distortions to emulate central vision loss. Following the simulation, participants completed a structured evaluation assessing perceived educational value, emotional impact, and potential applications in teacher training.ResultsParticipants reported a significant increase in their understanding of the challenges faced by students with low vision. The immersive experience was rated as highly educational, with all participants recommending its integration into teacher education programs. Qualitative feedback highlighted increased empathy and a deeper appreciation for the need for adaptive teaching strategies.DiscussionThe findings support the effectiveness of gaze-contingent XR simulation as a tool for enhancing teacher preparedness in inclusive education. The REALTER system offers a promising avenue for interdisciplinary collaboration between educators and vision specialists, contributing to more empathetic and informed pedagogical practices.